A formação docente no ensino da matemática e a tecnologia: um estudo sobre os desafios do mundo tecnológico - Lobato, Alcimara dos Santos (2023)
The research addresses teacher training in mathematics teaching in relation to technology and the challenges presented by the technological world. Teacher training in teaching Mathematics in the final years of Elementary School stands out regarding the world mediated by Digital Information and Communication Technologies (TDIC's), which instigate another/new way of teaching, learning to become a Mathematics teacher in the face of to technological advances. The research aims to understand how Mathematics teachers at a public high school are appropriating Digital Information and Communication Technologies (DICTs), not only from the point of view of their handling, but mainly from their pedagogical use. The qualitative and quantitative approach was used in the study, regarding the type of research, it was based on bibliographical study and field research, using the following instruments for data collection: observation and questionnaires. The research subjects consisted of ten final year mathematics teachers. The educational product developed was Continuing Training for Mathematics teachers in the final years of Elementary School whose objective is to enable Mathematics teachers to explore the Geogebra mathematical software as an instrument to facilitate mathematical learning. The conclusive analyzes of the research highlight the numerous problems related to school work, such as the lack of resources, government support, the continued training of mathematics teachers, the participation of parents, the difficulty of teachers in adapting to technologies and students assimilate mathematics content. Therefore, even in the face of the Pandemic and Post-Pandemic, education through technological means were ways of finding successful ways to mediate knowledge, especially in mathematics in a period of uncertainty.